2020
DOI: 10.3390/cells9020506
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Coupled Receptors in CNS: A Potential Therapeutic Target for Intervention in Neurodegenerative Disorders and Associated Cognitive Deficits

Abstract: Neurodegenerative diseases are a large group of neurological disorders with diverse etiological and pathological phenomena. However, current therapeutics rely mostly on symptomatic relief while failing to target the underlying disease pathobiology. G-protein-coupled receptors (GPCRs) are one of the most frequently targeted receptors for developing novel therapeutics for central nervous system (CNS) disorders. Many currently available antipsychotic therapeutics also act as either antagonists or agonists of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 199 publications
(234 reference statements)
2
59
0
Order By: Relevance
“…But research over the last several decades demonstrates additional models of GPCR signaling including G-protein coupled receptor kinases (GRKs) and β-arrestins ( 71 , 72 ) and homo- and hetero-dimerization of monomeric GPCR molecules ( 73 , 74 ). Despite the structural and general function commonality of GPCRs, individual GPCRs are extremely functionally diverse given the wide variety of ligands and stimuli they respond to, including but not limited to: biogenic amines, hormones, peptides, cations, lipids, glycoproteins, pheromones, synthetic drugs, tastes, odors, stress, and light ( 75 , 76 ). Therefore, activation of GPCRs can lead to various effects on cellular function, including cell homeostasis, intra- and extracellular signaling, and physiology at a macro level; and initiation/termination of transcription, activation of ion channels and neuronal excitability, and hormone release at a micro level.…”
Section: Systems Communication In Social Attachment: Oxytocinergic Dmentioning
confidence: 99%
“…But research over the last several decades demonstrates additional models of GPCR signaling including G-protein coupled receptor kinases (GRKs) and β-arrestins ( 71 , 72 ) and homo- and hetero-dimerization of monomeric GPCR molecules ( 73 , 74 ). Despite the structural and general function commonality of GPCRs, individual GPCRs are extremely functionally diverse given the wide variety of ligands and stimuli they respond to, including but not limited to: biogenic amines, hormones, peptides, cations, lipids, glycoproteins, pheromones, synthetic drugs, tastes, odors, stress, and light ( 75 , 76 ). Therefore, activation of GPCRs can lead to various effects on cellular function, including cell homeostasis, intra- and extracellular signaling, and physiology at a macro level; and initiation/termination of transcription, activation of ion channels and neuronal excitability, and hormone release at a micro level.…”
Section: Systems Communication In Social Attachment: Oxytocinergic Dmentioning
confidence: 99%
“…This condition may facilitate the binding of endogenous ligands and agonists to 5-HT 1A receptors (May et al, 2007;Saleh et al, 2018). Indeed, the allosteric condition of CBD may represent a novel therapeutic strategy to influence the effects of 5-HT 1A receptors (Azam et al, 2020). Radioligand binding assay revealed differences in IC 50 of CBD between hippocampus and temporal neocortex.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has found that pathway of GPCR was overrepresented and it is associated with pediatric obesity [35]. As a potential therapeutic target for intervention in cognitive deficits, the association of GPCR signaling pathway with BMI could reflect the intrinsic connection between cognition and obesity [36,37]. Table 3 also contains significant pathways directly related to metabolism of lipids, lipoproteins and carbohydrates, etc.…”
Section: Discussionmentioning
confidence: 99%